Real-time behavioral monitoring of C57BL/6J mice during reproductive cycle - Khatiz, Ariane; Tomlinson, Cassidy; Ruzhytska, Bohdana; Croft, Erika Kathe; Amrani, Abdelaziz; Dunn, Shannon; Mendrek, Adrianna; Gris, Denis (Frontiers in Neuroscience, 2025)
IntroductionThe present study aims to identify differences in behavioral profiles in post-pubertal C57BL/6J males and female mice across distinct phases of the reproductive cycle in a home cage environment.MethodsTo reduce human bias, we used an automated behavioral analysis system HomeCageScan from CleverSys Inc. Mice were monitored continuously, and resulting data were summarized across 24-h, light, and dark cycles. Behavioral activities of each period were analyzed using hierarchical clustering, factor analysis, and principal component analysis.ResultsFemales exhibited higher levels of physically demanding activities, including ambulatory and exploratory movements, particularly during estrus and metestrus, with estrus showing up to 30% more activity than males. In contrast, males consistently engaged in more sleep-related behaviors across all phases, with significantly higher engagement during the light cycle compared to females in proestrus and estrus (p < 0.0001); the extent of this sex difference was greater during proestrus and estrus than in metestrus and diestrus (p < 0.01). Notably, distinct patterns of sleep fragmentation were observed, with females experiencing greater disruptions during the light cycle, while males showed similar disruptions during the dark cycle. Feeding and resourcing behaviors were highest in males, showing up to 20% increase compared to cycling females, as well as significantly engaging in habituation-related behaviors such as feeding and digging. Interphase differences were observed within females, such as a significant increase of habituation-related activities during estrus compared to proestrus and diestrus (p < 0.05), while during the dark cycle, these activities peaked during the diestrus phase (p < 0.05). Female mice in the metestrus phase exhibited more sleep-related behaviors than those in proestrus.DiscussionOur study has revealed prevalent behavioral differences due to sex, and inter-phase variations by employing a continuous monitoring approach designed to reduce bias. This methodology ensures a comprehensive understanding of natural behavioral patterns and strategies.